On the Inefficiency of Inequality - Maurice Schiff (Institute for the Study of Labor (IZA), 2004)
A number of studies have examined the implications of preference interdependence. This paper models utility as depending on other people?s consumption levels and shows that welfare declines with inequality, equilibrium inequality is inefficient, and the optimal intervention leads to a more equal distribution.
Keywords: H21; H23; 330; inequality; efficiency; Verteilungstheorie; Konsumentenverhalten; Konsuminterdependenz; Einkommensverteilung; Wohlfahrtseffekt; Theorie